2022
DOI: 10.1038/s41598-022-14857-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced propagation of Granulicatella adiacens from human oral microbiota by hyaluronan

Abstract: Host determinants for formation/composition of human oral microbiota remain to be clarified, although microorganisms entering the mouth cannot necessarily colonize the oral environment. Here we show that human oral-abundant bacteria degraded host glycosaminoglycans (GAGs) in saliva and gingiva, and certain bacteria significantly grew on hyaluronan (HA), a kind of GAGs. Microbial communities from teeth or gingiva of healthy donors assimilated HA. Metagenomic analysis of human oral microbiota under different car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Our epidemiologic study was designed to provide a cross-sectional description of the abundances of different oral bacterial taxa in the mouth and was not designed to identify pathways by which they influence HIV pathogenesis. Nevertheless, two of the oral taxa, Streptococcus and Granulicatella , which we found to be more abundant in CWH, are known to degrade Hyaluronan (hyaluronic acid) an enzyme, which may help reduce the virulence of infections [41]. Abundance of Granulicatella in the mouth has also been linked to salivary levels of the proinflammatory cytokine IL-8 [42].…”
Section: Discussionmentioning
confidence: 80%
“…Our epidemiologic study was designed to provide a cross-sectional description of the abundances of different oral bacterial taxa in the mouth and was not designed to identify pathways by which they influence HIV pathogenesis. Nevertheless, two of the oral taxa, Streptococcus and Granulicatella , which we found to be more abundant in CWH, are known to degrade Hyaluronan (hyaluronic acid) an enzyme, which may help reduce the virulence of infections [41]. Abundance of Granulicatella in the mouth has also been linked to salivary levels of the proinflammatory cytokine IL-8 [42].…”
Section: Discussionmentioning
confidence: 80%
“…suggested that saliva glycosaminoglycans contribute to the formation and composition of the oral microbiota, influencing not only colonization but also adaptation to the host niche. Hyaluronan, for instance, has been found to enhance the proliferation of Granulicatella adiacens (Yabuuchi et al., 2022). Saliva includes various buffering systems, including those based on phosphate and bicarbonate, to maintain the intraoral pH around neutrality, thus providing a stable environment for oral bacteria (Wade, 2021).…”
Section: The Roles Of Three Components In the Oral–microbiota–brain Axismentioning
confidence: 99%